GSH-Px, G6PD and Arginase Activities and Some Biochemical Parameters in Cattle Infected with Theileria annuluta - Ozan, Sema Temizer; Yaralio?lu, Sema; Yilmaz, Seval; Özer, Edip; Şaki, Cem Ecmel; Sevgili, Murat (My University, 1999)
Theileria annuluta, for which Hyalomma tick species serve as intermediate host, causes an economically important disease in cattle 15 cattle infected with T.annulata and 15 healthy cattle were used in the study. The activities of glutathione peroxidase (GSH-Px), glucose 6 phosphate dehydrogenase (G6PD) and arginase that play role in the free radical metabolism in erythrocytes, and serum aspartate transaminase (AST), alanine transaminase (ALT), total billirubin, cholesterol trigliserid, total protein, albumin, urea, uric acid, haemoglobin, haematocrit levels were measured. Erythrocyte GSH-Px and G6PD activities were measured by beutler, arginase activitiy by the modified TDMU method and other serum parameters were evaluated in the Tecnicon RA-XT otoanalyser. While GSH-Px and arginase activities were found to be lower in the infected group than the control group (p<0.005), there was no statistically significant difference in the G6PD activity between the groups (p>0.005). While there was an increase in AST, ALT, total billirubin, direct billirubin, cholesterol, urea, heamoglobin, haematocrit values in the infected group compared to the control group (p<0.005), no significant changes were observe in trigliserid, total protein, uric acid, albumin values (p<0.005). If can be concluded that GSH-Px antioxidant system may be inadequate in cattle infected with T.annulata.
Theileria annulata ile Enfekte Si?irlarda GSH-Px, G6PD, Arginaz Aktiviteleri ile Bazi Biyokimyasal Parametreler
Keywords: Arginase; Glukoz-6-phosphate dehydrogenase; Glutathione peroxidase; Theileria annulata